Foreign Aid and Revenue Response : Does the Composition of Aid Matter? - Pivovarsky, Alexander; Clements, Benedict; Gupta, Sanjeev; Tiongson, Erwin (Washington, D.C. : International Monetary Fund, 2003)
This paper examines the revenue response to inflows of foreign aid in 107 countries during the period 1970-2000, In particular, it investigates whether the impact of aid on the revenue effort depends on the composition of aid (grants vis-a-vis loans). The results indicate that while concessional loans are associated with higher domestic revenue mobilization, the opposite is true of grants. On average, the dampening effect of grants on the revenue effort is modest. However, for those countries plagued by high levels of corruption, our results suggest that the decline in revenues completely offsets the increase in grants. The results are robust to various specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet